Study of the monte–carlo fault injection simulator to measure a fault derating. Issue 3 (21st January 2019) - Lee, Dong‐Woo; Na, Jong‐Whoa
Abstract : The SER of the selected circuits can be determined via radiation tests. However, the time and costs required to perform radiation tests are prohibitive. Here, the authors introduce an accelerated Monte–Carlo fault injection (MCFI) method that can solve the slow execution time problem of the previous MCFI method using a modified simulator that uses the Verilog Procedural Interface (VPI). To demonstrate the performance of authors' accelerated MCFI tool, the authors perform a fault‐injection campaign using the ISCAS85 and ITC99 benchmark circuits. Compared with the results from previous studies, the authors obtain an accurate logical derating rate value with a 3% variance, and the authors accelerate the execution time by 20 times or more.